PENGARUH KARAKTERISTIK INDIVIDU DAN ETOS KERJA TERHADAP KINERJA PEGAWAI PADA SEKRETARIAT DAERAH KABUPATEN SIMALUNGUN - Roy Sahputra Saragih; Nancy Florida Siagian (Jurnal Ekonomi dan Bisnis (EK&BI), 2020)
This study aims to determine and analyze (1) the effect of individual characteristics on employee performance; (2) the influence of work ethic on employee performance; (3) the influence of individual characteristics and work ethic on employee performance. The method used in this research is to use quantitative analysis methods. Sampling in this study using the Slovin method. The number of samples in this study were 70 employees of the Regional Secretariat of Simalungun Regency From the research results, the following results can be obtained: (a) the multiple regression results are Y 'Y' = 10.107 + 0.330X1 + 0.504X2; (b) the results of the t test (partial) show that each individual characteristic variable (X1) and work ethic (X2) have a significant effect on employee performance (Y), where the value of t count> t table (0.235) and the value of 'Sig' respectively -Each individual characteristic variable (X1) is 0.014 and work ethic (X2) is 0.001 <0.05. (c) the output model summary (R Square value) is 0.282, meaning that variations in employee performance can be explained by variations in individual characteristics (X1) and work ethic (X2)% and the rest is explained by other variables not examined. (d) From the calculation of the Fcount value of 13,146> the FTabel value of 3.13 or if it is seen from the sig 'value of 0.000 <0.05 then H0 is rejected.